Increased Expression of Dentin Matrix Proteins and Connexin43 is Associated to Reactionary Dentin Formation in Fluoride Exposed Rats - Fontanetti, Pablo Alejandro; Interlandi, Victoria; Ponce, Rubén Hugo; Gallará, Raquel Vivian; Centeno, Viviana Andrea (2022)
Fil: Fontanetti, Pablo Alejandro. Universidad Nacional de Córdoba. Facultad de Odontología. Departamento de Biología Bucal; Argentina.